(untitled) (Colloquia Comparativa Litterarum, 2025)
In the Western European novel, the death of the nobleness of the soul brings to life the “social realism” characteristic of Balzac’s work. This change is signified by the transformation of the novel’s protagonist from a moral into a social individual (S. Hadzhikosev). Later, this development will logically progress into the ascension of the antihero and conclude with the “cynical realism” (“réalisme cynique”), preached by authors like Frédéric Beigbeder. Reflecting on several major novels written in the 19th and 20th centuries, this article strives to answer the principal question of whether the novelist could take another realistic path, and tries to imagine what this path would look like.